2002
DOI: 10.1152/ajpendo.00261.2001
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid gland volume increases with postmaturational aging in the rat

Abstract: To examine the pathophysiology of the age-related rise in the plasma concentration of parathyroid hormone (PTH), we studied the relationships among plasma immunoreactive PTH (iPTH), parathyroid gland volume, parathyroid cell proliferation rate, renal function, and blood Ca 2ϩ in male Fischer 344 rats aged 6-28 mo. Plasma iPTH increased 2.5-fold between 6 and 28 mo and correlated with parathyroid gland volume (r ϭ 0.87). Gland volume began to increase as early as 6-12 mo of age and by 28 mo was threefold greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…2E) suggests that filtering function of the kidney glomerulus is maintained in our aged rats. This finding is consistent with a previous study showing unchanged Cr clearance in 24-month-old rats that is the same age as used in the present study; however, more aged, i.e., 28-month-old rats showed decreased clearance (Halloran et al, 2002) that is also consistent with human observations (Pattanaungkul et al, 2000). In drug treatment study, although HJG did not affect urinary volume and Cr concentration, it decreased urinary Ca concentration, which led to the result showing that HJG decreased total amount of excreted Ca into urine (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…2E) suggests that filtering function of the kidney glomerulus is maintained in our aged rats. This finding is consistent with a previous study showing unchanged Cr clearance in 24-month-old rats that is the same age as used in the present study; however, more aged, i.e., 28-month-old rats showed decreased clearance (Halloran et al, 2002) that is also consistent with human observations (Pattanaungkul et al, 2000). In drug treatment study, although HJG did not affect urinary volume and Cr concentration, it decreased urinary Ca concentration, which led to the result showing that HJG decreased total amount of excreted Ca into urine (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…The serum cCa levels also tracked slightly lower in younger patients (ESM Fig. 2), which might reflect a relationship between younger age and greater parathyroid gland sensitivity/PTH secretory potential [13][14][15][16], although this has yet to be confirmed in the context of SHPT. As in the prior 52-week study [17], we found no differences in the efficacy and safety of etelcalcetide when patients were divided into subgroups according to their dialysate Ca concentration (Tables 3 and 5).…”
Section: Discussionmentioning
confidence: 96%
“…Due to decreased dietary calcium intake and its diminished absorption from the small intestine in elderly (8), accompanied with an increase in PTH concentration (13), calcium supplementation is widely used for the prevention and treatment of advanced-age osteoporosis (10). In the present study, we investigated the effects of chronic Ca 2+ treatment on the structure and function of PTG, NaPi 2a and PTH1R in the proximal kidney tubules of middle-aged male orchidectomized rats, as an animal model of the andropause.…”
Section: Discussionmentioning
confidence: 99%
“…The main regulators of synthesis and secretion of PTH are low serum Ca 2+ concentration, mediated through calcium-sensing receptor (CaR) (12), and high serum phosphorus (Pi). Halloran et al (13) established that PTG volume and serum PTH level increase in both rats and humans during ageing. Increased PTH level contributes to bone loss and also induces phosphaturia (14,15), by binding to parathyroid hormone receptor type 1 (PTH1R) in bone tissue and epithelial cells of the kidney proximal tubules.…”
Section: Introductionmentioning
confidence: 99%